Perubahan Struktur Ekonomi Malang Dari Masa Ke Masa - Franciska Christiana; Nur Fakhri Febriansyah; Muhammad Yasin (Student Scientific Creativity Journal, 2023)
Economics is an interesting field of study if studied from a historical perspective, in its journey, Malang apparently is not only the center of coffee plantations. Malang at that time had a large sugar factory (PG). As the economy of Malang City grew, the number of sugar factories continued to increase. This transformation extends to the trade and service sector which has brought Malang to play an important role as one of the pillars of the economy in East Java. In this research, the author used a qualitative method. The key to the successful evolution of the Malang region’s economy is the synergy of political authority (government), the central bank as the monetary authority (BI Malang), and business actors so that they can become a transformative collective force in developing programs with an insight into regional potential and the institutional capacity of the local community, to the ability to adapt and capture new opportunities that arise in a rapidly changing economic order and environment is developed.